MANAJEMEN HUMAS DALAM MENINGKATKAN CITRA SEKOLAH DASAR ISLAM SURYA BUANA DINOYO KOTA MALANG - Karnoto, Ahmad (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
Public relations is a continuous effort to increase understanding between an institution and the community. Apart from that, public relations tries to make the image of the madrasah be seen as good by the public, or society. This is intended so that madrasas can survive and become more creative and useful for others. Progress in various fields has allowed public relations to emerge in its modern form. In the modern era, managing educational institutions requires combining promotional and marketing strategies with social interests. In research entitled "Public Relations Management in improving the image of the Surya Buana Dinoyo Islamic Elementary School, Malang City". The focus of this research is how public relations planning will improve the image of the Surya Buana Dinoyo Islamic Elementary School, Malang city, how the implementation of public relations will improve the image of the Surya Buana Dinoyo Islamic Elementary School, Malang city, and what the results of public relations management will be in improving the image of the Surya Buana Dinoyo Islamic Elementary School, Malang city. The research method used in this research is qualitative using observation, interview and documentation techniques. The research uses descriptive analysis which aims to describe the conditions in the field. Meanwhile, this type of research is descriptive qualitative research. The research results show that: public relations steps in improving the image of Surya Buana Islamic Elementary School are carried out through planning, implementation, and results/evaluation. 1) Public Relations has good relations with government/other agencies, 2) Good relations with parents of students, 3) Increase in the number of new students attending Surya Buana Islamic Elementary School compared to last year, 4) Documentation is running well even with human resources which is inadequate, 5) Social media has increased in terms of followers and viewers, 6) Website media has been run well but there is still a lot that can be developed in terms of appearance and content. Keywords: Public Relations, Image, School.